Scent of a Game - "Chandra, Raghav" (New Delhi, 2014)
Tsunami in the Jungle! Burree Maada, the famous Royal Bengal tigress, the pride of the tiger gene-pool, is mysteriously missing from the height-security of the Kanha Tiger Reserve. Mystery thickens as an old man's surreal dream about his son, Ram - a highly successful NRI settled in Silicon Valley being ravaged by a tiger uncannily begins to come true; Ganga, a brilliant Forest officer protecting tigers, is unceremoniously transferred; Sherry, a vivacious investigative journalist, is attacked repeatedly by the wildlife mafia; and a debonair Maharaja and his royal guests plan to recreate old-time tiger-shikar, with deep, dark vengeance in mind. Set against the backdrop of wildlife conservation, Scent of a Gameis a chronicle of tiger-poaching, big-game hunting and the international trade in endangered species worth billions of dollars. With its stark and unsettling storyline, this mystery-thriller transforms our understanding of not just the tiger and our environment but life itself.
Keywords: Fiction